The preoperative and postoperative experiences of mastectomy patients with and without neoadjuvant therapy - Esteban, Marcus Juan L.; Bautista, Fraingeli Camille D.; de Lemos, Marian Angelica V.; Dumlao, Lenore Anne D.; Fabregar, Anton Carlo O.; Lisondra, Lady Nancy C.; Montalbo, Maricor C.; Ortega, Giselle A.; Rigunay, Maria Carmela T.; Toribio, Dianne M.; Untalasco, Zyena Joyce P.; Valdez, Aileen Mae C. (Manila College of Nursing University of the Philippines Manila, 2008)
This research aimed to describe the perioperative experiences between patients who underwent mastectomy with neoadjuvant therapy and those without neoadjuvant therapy in terms of anxiety levels and post-operative wound conditions.

A descriptive design was used. The sample size is eleven — three in the neoadjuvant group and eight in the non-neoadjuvant group. The translated A-State and A-Trait tool was used to measure anxiety levels among respondents.

The respondents belong to the 42-60 age range where seven of eleven are married. It was observed that in terms of post-operative wound characteristics most participants did not show any change from the first post-operative to the second post-operative measure. If there were changes, it was observed that the change was always from a higher level to a lower level, example from moderate to low level pain. It was also observed that those who underwent neoadjuvant therapy had lower levels of anxiety than those who did not. It was also observed that A-Trait scores showed less drastic change and were more stable than A-State scores. It was also observed that the mean of A-Trait scores for both neoadjuvant and non-neoadjuvant groups showed an increase from the preoperative to the post-operative period. This pattern was not observed for A-State. The results however are inconclusive due to limitations of the study in terms of research design and sample size.

It is recommended that the factors be analyzed further and that a larger sample size be used so results would be more conclusive and generalizations can be made. It is also recommended to explore the pre and post-operative experiences of other surgeries which utilize neoadjuvant therapy.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, 2008.
Keywords: Nursing -- Research